Songs of innocence a child's view of family life (Victoria : The Australian Children's Television Foundation, 1992)
A documentary featuring 13 children from Melbourne families, talking candidly and movingly about the often painful business of growing up in diverse family structures
Executive producers, Patricia Edgar, Harry Bardwell
Keywords: Children -- Family relationships; Family; Children